Recent Advances in High Pressure Processing of Milk and Milk Products - A review - Theo Varzakas; Merve Severoğlu; Sofia Agriopoulou; Hamdi Barbaros Özer (Journal of Agricultural Sciences)
As the global consumers’ demand towards minimally processed freshlike foods has been continuously increasing, efforts to develop novel food processing technologies have been intensified. Among non-thermal food processing technologies, high pressure processing (HPP) seems to be more advantageous due to its environmentally friendly nature, cost efficiency, suitability for processing foods in any form and its positive impacts on foods’ shelf-life as well as providing efficient microbial safety. Microbiological inactivation efficiency of HPP has been well documented but the role of this technology in digestion efficiency of milk compounds is yet to be elucidated in detail. Also, the potential safety hazards and challenges of HPP in foods require more intense studies. This review deals with the recent developments in HPP treatment to milk and milk products.